2010
DOI: 10.1038/ncb2078
|View full text |Cite|
|
Sign up to set email alerts
|

Plasma membrane contributes to the formation of pre-autophagosomal structures

Abstract: Autophagy is a catabolic process where lysosomes degrade intracytoplasmic contents transported in double-membraned autophagosomes. Autophagosomes are formed by elongation and fusion of phagophores, which derive from pre-autophagosomal structures. The membrane origins of autophagosomes are unclear and may involve multiple sources, including the endoplasmic reticulum and mitochondria. Here we show in mammalian cells that clathrin heavy-chain interacts with Atg16L1, and is involved in the formation of Atg16L1-pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
655
4
7

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 783 publications
(705 citation statements)
references
References 31 publications
(51 reference statements)
29
655
4
7
Order By: Relevance
“…CLTC is also present on mature autophagosomes, colocalizing with LC3B during initiation of autophagy [22]. Additionally, given that CLTC has been shown to interact with ATG16L1, which mediates earlier stages of autophagosome development, it is possible that CLTC may also contribute to other stages of autophagy [20]. In this study, Coxiella is used as a tool to demonstrate that fusion of autophagosomes with lysosomes involves CLTC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CLTC is also present on mature autophagosomes, colocalizing with LC3B during initiation of autophagy [22]. Additionally, given that CLTC has been shown to interact with ATG16L1, which mediates earlier stages of autophagosome development, it is possible that CLTC may also contribute to other stages of autophagy [20]. In this study, Coxiella is used as a tool to demonstrate that fusion of autophagosomes with lysosomes involves CLTC.…”
Section: Discussionmentioning
confidence: 99%
“…A link between CLTC and autophagy has recently been discovered with the observation that CLTC is required both for autophagosome formation and in the later stages for regulation of autophagic lysosomal reformation [20,21]. In addition, it has been reported that CLTC colocalizes with LC3B upon induction of autophagy [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Membranes derived from the Golgi, endoplasmic reticulum, mitochondria, and plasma membrane have been implicated as the source membranes. [20][21][22][23][24][25] It is possible that vesicles from multiple membrane sources may fuse heterotypically to generate APs. This early fusion steps may involve lipidhydrolyzing enzymes, possibly PLD.…”
Section: Discussionmentioning
confidence: 99%
“…Although evidence supports the idea that nucleation of the isolation membrane occurs at a distinct site emanating from the endoplasmic reticulum (ER), termed the omegasome 17 , other sources of membrane contribute to autophagosome formation, including ER-Golgi intermediate compartments, ERmitochondri a junctions, mitochondria, endosomes and the plasma membrane [17][18][19][20][21][22] . Taken together, these studies highlight the complexities of autophagy initiation in mammals.…”
Section: Overview Of the Autophagic Pathwaymentioning
confidence: 99%